An investigation of deformation and failure mechanisms of fiber-reinforced composites in layered composite armor. (1st February 2022) - Guo, Guodong; Alam, Shah; Peel, Larry D.
Abstract: This paper aims to study the deformation characteristics and failure mechanisms of fiber-reinforced polymer composites used in layered composite armor under ballistic impact. A Kevlar-29/epoxy composite and an ultra-high molecular weight polyethylene (UHMWPE) fiber-reinforced composite backed bilayer ceramic armor were respectively impacted against 7.62 mm APM2 projectiles at several different velocities. The dependence of failure mechanisms on impact velocity was analyzed both experimentally and numerically. Ballistic tests revealed that the Kevlar-29/epoxy composite backed armor displayed a lower perforation velocity than the UHMWPE fiber reinforced composite backed armor. However, under non-perforated impacts, the UHMWPE fiber reinforced composite exhibited a much higher back face deflection (BFD). According to the post-mortem visual and SEM analysis, the failure of the Kevlar-29 fiber was dominated by shear plugging in the front layers and fiber tensile breakage in the rear layers, whereas in the UHMWPE fiber reinforced composite, failure was dominated by shear plugging initiated from the front layers. These results suggest that the UHMWPE panel is more effective in resistant fiber tensile breakage which usually occurs on the back side of the panel. Using the Ls-dyna explicit dynamic finite element (FE) program, the ballistic behavior of a layered armor backed by a hybrid panel with varying mix ratios was studied numerically. The results show that using high tensile resistant fiber in the rear layers can effectively prevent fiber tensile failure and using high shear resistance fiber in the front layers can effectively prevent shear failure. These results are valuable in making the best use of fiber-reinforced composites in advanced armor design.